Euro and capital markets : a new era - Perée, Eric (2001)
Examines the forces that have changed the financial landscape at the world level over the last two decides. Summarizes the arguments of how the introduction of the euro should add to these broader economic forces in reshaping euro financial markets. Verifies whether the actual experience since January 1999 has been in line with the ex ante expectations.